사라진 제목 - 무제(Untitled)에 대한 미술사적 고찰 - 김석모; Kim Sukmo (인문학연구, 2025)
현대미술에서 ‘무제(Untitled)’는 가장 널리 사용되는 작품 제목 중 하나이다. 언뜻 보기에는 단순한 명명의 부재처럼 보이는 이 형식은, 실상 작가의 창작 태도, 미학적 전략, 해석에 대한 태도, 그리고 제도적 조건들에 대한 비판적 입장을 포괄하는 복합적인 의미망 위에 놓여 있다. 본 논문은 무제라는 제목 형식이 등장하고 반복적으로 선택되는 미술사적 맥락을 고찰하며, 그것이 단순히 작명에 실패했거나 회피한 결과가 아니라, 창작자의 의도적인 결정이자 비판적 태도임을 밝히고자 한다. 19세기 후반부터 시작된 미술의 자율성 강화와 예술가 주체성의 부상은 작품 제목을 단순한 식별의 수단에서 창작 행위의 연장 선상에 놓이게 만들었다. 이러한 흐름 속에서, 추상미술과 전위예술의 전개는 제목의 해석적 개입을 문제시하며 그 최소화를 시도하였고, 특히 미국의 추상표현주의 작가들은 감각적 경험과 실존적 표현을 방해하는 요소로서 언어의 역할을 경계하였다. 무제라는 제목은 이와 같은 맥락에서 해석의 유도와 개입을 지연시키고, 감상자의 직관적 몰입을 유도하는 미학적 수단으로 기능하게 되었다. 특히 1960년대 미니멀리즘의 전개 과정에서 무제는 단지 언어의 소극적 부재를 넘어, 작품을 외부 세계와의 지시적 관계로부터 완전히 분리하고 오직 물리적, 지각적 존재로 제시하려는 적극적인 탈기호화 전략으로 자리 잡았다. 본 논문은 무제라는 제목의 사용이 미술사적, 제도적, 해석학적 맥락에서 어떤 의미를 획득하며 전개되어 왔는지를 다양한 사례와 문헌 분석을 통해 탐색한다. 특히 추상표현주의의 미학적 배경, 도널드 저드의 무제 원칙, 전시현장에서 발생한 제목 부여의 관습과의 충돌, 그리고 미술 시장의 요구가 어떻게 작가의 무제 전략과 긴장 관계를 형성했는지를 살펴봄으로써 현대미술에서 무제가 갖는 미술사적 함의를 포괄적으로 이해할 수 있는 새로운 해석 틀을 제시하고자 한다. In contemporary art, “Untitled” is one of the most commonly used titles for artworks. Although it may appear as a mere absence of naming, this form actually rests upon a complex network of meanings that encompass artists’ creative attitudes, aesthetic strategies, approaches to interpretation, and critical stances toward institutional conditions. This research examines the art-historical context in which the title “Untitled” emerged and was repeatedly chosen, revealing that it is not simply a result of failure or avoidance in titling but an intentional aesthetic decision and a critical posture. Since the late 19th century, art titles evolved from labels to creative elements. Abstract and avant-garde artists, especially American Abstract Expressionists, saw language as disruptive, using “Untitled” to minimize interpretation and encourage intuitive viewer engagement. In particular, during the rise of Minimalism in the 1960s, “Untitled” went beyond the passive absence of language to become an active strategy of de-signification, seeking to separate the work completely from external references and present it solely as a physical and perceptual entity. This paper examines the use of “Untitled” in contemporary art, focusing on its historical, aesthetic, and institutional meanings. Through case studies on Abstract Expressionism, Donald Judd, exhibition practices, and the art market, it offers a new framework to understand the role and significance of untitled works.